Challenges, Benefits, And Opportunities Of Indonesian Female Peacekeepers - Isnarti, Rika; Kamayi, Astra; Anggorowati, Ani (RMPI-BRIN, 2023)
The adoption of Resolution on Female Peacekeepers (Resolution 2538) by the United Nations (UN) Security Council in 2020 signifies Indonesia’s commitment to increasing women’s participation in peacekeeping and their global contributions to peace. Indonesia has a strong track record in peacekeeping, ranking among the top 10 troop contributors by deploying military, police, and expert personnel. Despite prevailing stereotypes that associate warfare with men and view women as vulnerable, women play a crucial and unique role in peacekeeping missions. This article examines the challenges, benefits, and opportunities for Indonesian women in the military who engage in peacekeeping. The research methodology involved interviews with male and female members of the Tentara Nasional Indonesia (TNI) who have served as peacekeepers, as well as the permanent representatives of Indonesia at the UN. Additionally, existing studies on Indonesian women in peacekeeping were reviewed. The research reveals significant challenges faced by Indonesian women in peacekeeping, including limited interpersonal and intercultural communication skills, organizational culture, and biases. Overcoming these challenges is crucial for personal and international benefits. On the other hand, opportunities for enhancing the role of Indonesian women in peacekeeping include promoting kindness and friendliness and implementing regular military practices in local communities. In conclusion, Indonesia’s Resolution on Female Peacekeepers highlights the responsibility of Indonesia to enhance women’s participation in peacekeeping missions. By addressing the challenges and leveraging the opportunities identified, Indonesia can further strengthen its contributions to peacekeeping through the active involvement of women.